Banyuwangi Regency Government Policy Concerning Corporate Social Responsibility in An Improvement Effort Cultural Tourism - Imaniar, Dimas (Iapa Proceedings Conference, 2024)
This research design is about how companies use social responsibility as a form of ethics to improve performance in the long term. Entrepreneurs, governments and society as a whole must ensure that companies are socially responsible. Companies have a social responsibility that is not only limited to providing funds for cultural improvement programs, but also treating their employees well, building long-term relationships with the environment, and running sustainable programs. The urgency of this research is expected to be able to provide direction to companies to carry out social responsibility in making policies and making decisions in accordance with regional government policies that support regional cultural tourism. Companies have an obligation to make policies, take decisions, and do things that are beneficial to society, which is known as social responsibility. Organizational strategies, structures and systems, as well as cultural and organizational strengths achieve organizational goals. The theories raised include the theory of social responsibility and local culture, as well as the reformulation theory of government policy design. By using a qualitative descriptive analysis method supported by interviews, documentation and focus group discussions (FGD), it is hoped that it can provide solutions to reformulate government policies that can support cultural tourism through corporate social responsibility. This research aims to reformulate the draft government policy regarding corporate social responsibility to lead and support Banyuwangi regional culture in an effort to improve the community's economy and the Banyuwangi cultural tourism industry. The output of this research is to provide a policy design reformulation to the Banyuwangi government regarding corporate social responsibility.